2019
DOI: 10.1590/s1678-3921.pab2019.v54.00096
|View full text |Cite
|
Sign up to set email alerts
|

Steel slag and phosphate nutrition of corn inoculated with arbuscular mycorrhizal fungi

Abstract: The objective of this work was to evaluate the effect of the use of steel slag as a soil acidity corrective and of mycorrhizal fungi associated with phosphate fertilization on corn plants. The study was performed in a greenhouse, using 3-kg pots with a Typic Haplorthox, in a 4x5x2 factorial arrangement, with four acidity correction treatments (C1, correction with dolomitic limestone at a dose of 4 Mg ha-1; C2, correction with steel slag at a dose of 4 Mg ha-1; C3, correction with a 1:1 mixture of 2 Mg ha-1 dol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…Both correctives induced an increase in the soil Ca and Mg contents as the rates were increased, which was also observed by Nunes et al (2019). Between the correctives, limestone provided higher Mg levels in both soil layers, corroborating with Caetano et al (2016), despite the similar amounts of this nutrient in their composition.…”
Section: Soil Chemical Characteristicssupporting
confidence: 68%
“…Both correctives induced an increase in the soil Ca and Mg contents as the rates were increased, which was also observed by Nunes et al (2019). Between the correctives, limestone provided higher Mg levels in both soil layers, corroborating with Caetano et al (2016), despite the similar amounts of this nutrient in their composition.…”
Section: Soil Chemical Characteristicssupporting
confidence: 68%
“…This author also found similar efficiency between steel slag and dolomitic limestone in correcting the acidity of the soil. Also, Nunes et al (2019) found the same efficiency between steel slag and dolomitic limestone.…”
Section: Resultsmentioning
confidence: 65%
“…This result corroborates those of Sala et al (2007), who studied the interaction between AMFs and diazotrophic bacteria in wheat and determined that the isolated inoculation of Glomus Etunicatun and Acaulospora colombiana did not differ from the treatments without inoculation for the root dry mass of wheat. However, Rhizophagus Clarus and Gigaspora Margarita inoculation caused an increase in dry mass and root volume in maize (Zea mays) when compared to the control without inoculation (Nunes et al, 2019). This demonstrates the need to select AMF species based on these morphological traits.…”
Section: Figurementioning
confidence: 99%
“…The symbiosis established between arbuscular mycorrhizae and plant species is significant because AMF promote root elongation through their extraradicular hyphae, increasing the contact area in the soil, which can increase the specific surface area up to 40-fold (Giovannetti et al, 2001). As such, several benefits related to the greater specific surface area of plants through symbiosis with AMF are cited in the literature, including increased water and nutrient absorption with low soil mobility (Silveira et al, 2002), as well as resistance to biotic and abiotic stresses (Nunes et al, 2019). The average root diameter was higher for A. Colombiana, but the other mycorrhizal inocula and the control did not differ (Figure 3 F).…”
Section: Figurementioning
confidence: 99%